2016
DOI: 10.1038/srep34715
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cells attenuate 2,5-hexanedione-induced neuronal apoptosis through a NGF/AKT-dependent pathway

Abstract: Growing evidence suggests that the increased neuronal apoptosis is involved in n-hexane-induced neuropathy. We have recently reported that bone marrow-mesenchymal stem cells-derived conditioned medium (BMSC-CM) attenuated 2,5-hexanedione (HD, the active metabolite of n-hexane)-induced apoptosis in PC12 cells. Here, we explored the anti-apoptotic efficacy of BMSC in vivo. HD-treated rats received BMSC by tail vein injection 5 weeks after HD intoxication. We found that in grafted rats, BMSC significantly attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 42 publications
5
22
0
Order By: Relevance
“…We previously reported that BMSC transplantation improved motor functional recovery and alleviates pathological damage of axon and myelination in the spinal cord and sciatic nerve of HD-intoxicated rats 10 . To determine whether autophagy is involved in BMSC-afforded protection, we detected the alterations of autophagy in HD-treated rats with or without BMSC transplantation.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…We previously reported that BMSC transplantation improved motor functional recovery and alleviates pathological damage of axon and myelination in the spinal cord and sciatic nerve of HD-intoxicated rats 10 . To determine whether autophagy is involved in BMSC-afforded protection, we detected the alterations of autophagy in HD-treated rats with or without BMSC transplantation.…”
Section: Resultsmentioning
confidence: 93%
“…The potent protective effects displayed by conditioned medium prepared from BMSC (BMSC-CM) against HD-induced apoptosis were observed in PC12 cells, which was a rat pheochromocytoma cell line and possessed properties of neurons 9 . BMSC transplantation also attenuated HD-induced neuronal damage and improved the motor performance in rats 10 . However, the mechanisms responsible for BMSC-afforded neuroprotection remain unclear.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Roche's In Situ Cell Death Detection Kit (Roche, Mannheim, Germany) was used to perform TUNEL assays [17,21]. TUNEL + cells were observed using a uorescence microscope (400× magni cation).…”
Section: Tunel Assaymentioning
confidence: 99%